An approach for simultaneous computer-aided molecular design with holistic sustainability assessment: Application to phase-change CO2 capture solvents. (6th April 2020) - Papadopoulos, Athanasios I.; Shavalieva, Gulnara; Papadokonstantakis, Stavros; Seferlis, Panos; Perdomo, Felipe A.; Galindo, Amparo; Jackson, George; Adjiman, Claire S.
Highlights: A novel approach for simultaneous CAMD and holistic sustainability assessment. Consideration of 11 sustainability-related indicators, aggregating several impact categories. Systematic approach to address data gaps in property predictions using data mining. Application on the design of phase-change solvents for CO2 capture. Abstract: We propose an approach for the simultaneous consideration of a holistic sustainability assessment framework in computer-aided molecular design (CAMD). The framework supports the assessment of life cycle (LCA) and safety, hazard and environmental (EHS) impacts from cradle-to-gate of chemicals designed through CAMD. It enables the calculation of a total of 11 sustainability-related indicators, aggregating several impact categories. A lack of models and data gaps in property prediction are addressed through a data mining approach which deploys on-line similarity assessment against existing molecules. The LCA and EHS assessment are conducted simultaneously with CAMD or after CAMD to assess the designed solvents. A case study is presented on the design of phase-change solvents for chemisorption-based post-combustion CO2 capture. The proposed approach identifies verifiably useful phase-change solvents that exhibit favourable performance trade-offs compared to a reference CO2 capture solvent. The on-line use in CAMD of sustainability criteria favours the design of hydroxyl-containing solvents.